Stochastic analysis of combined primary-secondary structures subjected to imprecise seismic excitation - Sofi, Alba; Genovese, Federica (Engineering structures, 2025)
The imprecise stochastic process model is able to incorporate both random and epistemic uncertainties, leading to a more accurate description of environmental excitations, such as earthquakes or wind loads, when limited data are available. Epistemic uncertainties in the loading model may significantly affect the performance of structural systems. The present paper addresses the stochastic analysis of combined primary-secondary structures subjected to imprecise seismic excitation modeled as a zero-mean stationary Gaussian random process, characterized by an interval-valued Power Spectral Density (PSD) function. The power and energy content of the imprecise ground motion acceleration may vary, even for the same soil category, affecting the complex dynamic behavior of combined structures and the vibration control capacity of secondary substructures under different frequency tuning conditions. The main purpose of this study is to develop a framework for investigating both the influence of epistemic uncertainties in the loading model and the interaction effects between the subsystems on the seismic performance of combined primary-secondary structures. To this aim, the stochastic analysis of combined structures under imprecise ground motion acceleration is addressed in both the frequency and time domains by an efficient approach capable of decoupling the propagation of interval and random uncertainties. Seismic safety assessment is performed in the framework of the first-passage theory by interval extension. •Combined primary-secondary structures under imprecise seismic excitation are analyzed.•An interval-valued Power Spectral Density function is considered.•Interval first-passage reliability analysis of the combined structure is performed.•The propagation of interval and random uncertainties is efficiently decoupled.•The vibration control capacity of the secondary substructures is investigated.